Laboratory Investigation and Mechanical Evaluation on Xanthan Gum-Reinforced Clay: Unconfined Compression Test, Triaxial Shear Test, and Microstructure Characterization - Liangbo Ying; Mengqi Xu; Jiale Luo; Wei Wang (Buildings, 2025)
Xanthan gum (XG) has potential application prospects as a biopolymer in soil reinforcement engineering. However, there remains a lack of relevant research on its influence on the mechanical properties, microscopic mechanism, and pH value changes in clay. In this study, the effects of different XG dosages (0%, 5%, 10%, 15%, and 20%) on the microscopic mechanism, pH value, and mechanical strength of clay at the 7-day curing age were investigated through tests including Zeta potential, infrared spectroscopy, scanning electron microscopy (SEM), pH value, unconfined compressive strength, and triaxial shear strength. The results show that the addition of XG can not only promote charge exchange to generate hydrogen bonds and increase the bonding force between clays but can also form flocculent aggregates between the matrices, cementing the clay, filling the pores, and reducing the porosity of the samples. It can significantly increase the mechanical strength of the sample. When the content of XG is 20%, the unconfined compressive strength (UCS) and cohesion of the sample reach their maximum, increasing by 296% and 806%, respectively, compared with the reference group without XG. The conclusions drawn from this research can not only provide a theoretical reference for improving soft clay foundations but also expand the application research of XG in clay.